Koliščarji O koliščarjih in koliščarski kulturi Ljubljanskega barja - Velušček, Anton (ZRC SAZU, Založba ZRC, 2010)
This popular-science publication describes the pile-dwellings of the Ljubljansko barje, which were created in the first half of the 5th millennium BC. However, when the lake was completely overgrown with swamps and marshes (at the latest around the middle of the 2nd millennium), the construction of such settlements stopped. From then on, new settlements were built on the outskirts of the lake banks, where the fields were previously. There they also farmed livestock such as cattle, sheep, goats and pigs. They were accompanied by dogs. Hunting and fishing were also important economic activities~they harvested fruits in the forests. They made pottery vessels. Findings of copper and metallurgical articles, however, prove that at least since the 4th millennium BC they were engaged in copper metallurgy. Logboats were used to navigate the lake and in the second half of the 4th millennium even for routes outside the Ljubljansko barje. In short, they were very resourceful and were able to adapt well to the environment in which they lived.Only in Slovenian